Hydrological quantification of oil palm catchments for an improved streamflow modelling - Yusop, Zulkifli; Chong , Meng Hui; Abu Bakar, Siti Nurhidayu; Mohamed, Maketab; Mohd. Nasir, Kamarul Azlan; Nik, Abdul Rahim (Faculty of Chemical and Natural Resource Engineering, 2007)
Despite the encouraging numbers of hydrological studies conducted in Malaysia, relatively little quantitative information is available to date on the effects of establishing or replanting oil palm. The hydrological properties of oil palm catchments in Sedenak Estate, Johore, were examined by establishing three experimental catchments. Each catchment represents different growing stage of oil palm, i.e., C1 (2 years), C2 (5 years) and C3 (8 years). In general, the storm hydrographs of all catchments are flashy and comparable to forested catchments. The time to peak ranges from 5 to 115 minutes with an average of 53 minutes. On an evently basis, baseflow contributes between 65% and 74% of the total flow. Stormflow and peakflow are strongly correlated with rainfall. The threshold rainfalls that produce stormflow are very similar in all the three catchments, between 14.4 mm and 14.9 mm. Evapotranspiration (ET) rates were estimated using five methods, namely the Penman, Penman-Monteith, Blaney-Criddle, Short-time Period Waterbudget (SPWB) and Water Balance models. Among these models, the ET values estimated by Penman, Penman-Monteith and SPWB show comparable trends and magnitudes whilst the Blaney-Criddle gives relatively high values. On the other hand, the ET values derived from Water Balance show large fluctuations. It is possible to improve the ET estimates by taking into account the spatial variation in soil moisture. The newly planted catchment, C1 has better hydrological properties in term of Minimum Contributing Area (MCA) compared to the more established and matured catchment, C3. The higher MCA value in C3 is attributed to compacted ground surface due to the passage of fruit harvesting machinery and dying off of cover crop. It is important to establish cover crop species that are more shade tolerant to reduce surface runoff.